La protection de l'environnement au Canada et aux États-Unis - Piette, Jean (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1988)
This paper explains some of the main differences between the development and the structure of environmental legislation, regulations and programs in Canada and the United States. In Canada, the division of powers under the Federal Constitution between Parliament and Provincial Legislatures explains the structure and scope of Canadian environmental law. Federal laws and regulations have been mostly sectoral while Provincial laws have been broader and have been successful in integrating environmental planning instruments. U.S. environmental laws, regulations and programs are developed under the leadership of Congress. The Environmental Protection Agency and State Governments are called upon to play an important role in the implementation of Federal environmental statutes. Contrary to the Canadian situation, citizen suits and the Judiciary are instrumental in the development of U.S. environmental law.